Research, evaluation and audit : key steps in demonstrating your value - Grant, Maria J.; Sen, Barbara; Spring, Hannah (Facet Publishing, 2013)
This step-by-step guide provides encouragement, support and direction for health librarians who may be new to research and evaluation, or lacking in confidence or expertise. With a focus on practice based research, evaluation, and small projects it guides the reader through the research process from starting to think about the research question, through to the completion of the research and dissemination of the results. It is designed to encourage quality research from library professionals and encourage them to add to the evidence base in this sector. The book is structured into three parts: getting started; doing the research; and the impact of your research. Written by experts in the field, this timely edited collection considers methods and approaches that are suitable in a health library context, making it a useful tool for health library professionals and students alike.